Diversity, difference, equity: how student differences are socially constructed in Singapore. Issue 6 (2nd November 2021) - Heng, Tang T.; Lim, Leonel
ABSTRACT: Diversity is a socially constructed idea where differences are assigned values that are in turn shaped by local socio-political exigencies and narratives. Interpretations of diversity in Anglo-Saxon contexts tend to revolve around identity markers, such as race, gender, (dis)abilities and nationalities. Looking beyond Anglo-Saxon contexts, this paper examines how teachers in Singapore understand student diversity through their practices of differentiated instruction and, consequently, how these perceptions and practices engage with issues of equity. Teachers in our study interpreted student diversity primarily as academic readiness – shaped by students' abilities, attitudes and families. These teachers' experiences illuminate how analysing practices addressing diversity yields critical insights around dominant narratives and ideologies. In particular, findings point to a contextually situated construction of diversity and understandings of equity that are attuned to the national narratives of meritocracy, multiculturalism and academic excellence in Singapore.